PRACTICE GUIDELINES FOR THE INTEGRATION OF CHILD-HEADED HOUSEHOLDS INTO EXTENDED FAMILY FOLDS - Nziyane, Luzile Florence; Alpaslan, Assim Hashim (Social Work/Maatskaplike Werk, 2011)
Foster (2004:2) emphasises that even with the advent of the HIV/AIDS epidemic, the “extended family safety net is still by far the most effective response to economic and social crises throughout sub-Saharan Africa.” Webb (in Foster, Levine & Williamson, 2005:241) agrees that the extended family system, especially in sub-Saharan Africa, generally serves as an alternative arrangement to provide care to orphaned children. However, Foster (2004:2-3) states that this system is becoming stressed and its capacity to care for orphans may be weakening as some of the orphaned children do slip from this traditional method of orphan care and end up living by themselves in child-headed households (CHH). Phiri and Tolfree (in Foster et al., 2005:16-17) assert that these families need support to enable them to cope with the strain of shouldering the burden of taking in orphaned children. It is in light of this that the researchers were motivated to conduct the study to explore the suggestions on how barriers that hinder effective integration of these children into extended family folds can be overcome with a view to formulating practice guidelines to support this traditional method of orphan care